Dándole sentido a lo descontextualizado. Análisis de conglomerados óseos procedentes de Huaca Middendorf, Lima-Perú - Rojas Pelayo, Lisseth F. (2021)
Middendorf Huaca towards the end of the Early Intermediate Period and the beginning of the Middle Horizon (around AD 250-600), was part of the component of the Maranga Complex, a site close to the Lima society. This research focuses on the panorama of the disarticulated remains from this site, excavated by the Maranga Archaeological Project (PRAMA). The study sample comes from the south-central sector of the west platform, a space occupied by the clearing of ancient excavations, where disarticulated human remains from a population of the Lima period were recovered. This research aimed to characterize the population in paleo-demographic terms while providing methodological strategies focusing on the treatment of bone conglomerates as an analysis potential. Therefore, we could record and characterize 2928 skeletal elements in terms of their diagnostic features (minimum number of individuals [NMI], sex, age, pathologies, and injuries). This research focuses on the minor axis of «contextual value», although this is more limited, it provides demographic parameters information. Thus, we identified almost half a hundred individuals, of whom more than half were young, in which we recorded various degenerative and congenital pathologies ascribed to adult individuals, as well as injuries associated with non-lethal events.